Visualization of surface movement data using tin based temporal modeling approach - Mohd. Shafry Mohd. Rahim, author; Nur Zuraifah Syazrah Othman, 1982-, author; Daut Daman, author; IASTED International Conferencd on Advances in Computer Science and Technology (4th: 2008: Langkawi) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL